Human-computer interactions for systems identification of gene regulatory networks - Tan, Tian Wen (2017)
With technology so advanced these days, there is an increasing trend of a desire to make use of technology to understand and gain knowledge. This thirst for knowledge is greatly supported by humans’ curiosity in finding out how technology and science can complement each other. Where technology is the application of science, there is an increasing trend of people wanting to gain a concise understanding on biological data with the aid of technological tools. With Gene Regulatory Network (GRN) playing a major part of molecular processes, one popular software tool is the GRN tool which provides users with an interactive Graphical User Interface (GUI) to perform their desired actions like inferencing networks or modifying the inferred network. In this project, code review is to be done to better understand the software implementation, where explanations will then be made. Thereafter, analysis is carried out on the software implementation and enhancements to improve the user experience will be introduced. With this documentation created, detailed explanations are recorded in hopes of helping users to acquire a better understanding of this software, Meta GRN.